Fingerprint doorlock system using Arduino uno - Raghavendra, Rekha; Gowda, Shobha; Thomas, Jissy (The Scientific Temper, 2025)
Security continues to be a primary concern in homes, offices, and commercial establishments. Traditional locking mechanisms, such as mechanical key-based locks or password/pattern-protected systems, present notable vulnerabilities. Keys can be lost or duplicated, and passwords or patterns may be easily observed or compromised. These limitations highlight the need for more secure and intelligent access control solutions. This project proposes the design and implementation of a fingerprint-based biometric door lock system integrated with a buzzer alert feature. The system eliminates the need for carrying physical keys and enhances user convenience while significantly improving security. In the event of an unauthorized access attempt, the system triggers a buzzer to alert the owner, thereby adding a real-time security layer. Fingerprint locks have gained widespread acceptance due to their simplicity and improved safety over traditional locks. However, the growing sophistication of biometric tricking techniques necessitates the development of more robust systems. This study explores the incorporation of multiple biometric sensory system and advanced encryption algorithms to enhance the accuracy and resilience of fingerprint authentication. The proposed system not only strengthens access control but also addresses common issues associated with conventional locks. By combining biometric recognition with real-time alerts and secure data processing, the project aims to provide a comprehensive and reliable security solution. This approach offers a promising alternative for modern-day security needs, with potential applications in smart homes, secure workplaces, and high-risk environments.